Chemotherapy alone versus chemotherapy plus 125I brachytherapy for the second-line treatment of locally recurrent cervical cancer after/with radical treatment: A propensity score analysis - Zhimei Huang; Wang Yao; Zhihui Zhong; Guang Yang; Jihong Liu; Haifeng Gu; Jinhua Huang (Heliyon, 2024)
Rationale and objectives: The primary aim of this study was to conduct a retrospective comparative analysis of the survival outcomes in patients with recurrent cervical cancer (CC). Specifically, we aimed to compare the efficacy of chemotherapy alone versus the combined approach of chemotherapy and 125I brachytherapy subsequent to the failure of initial chemotherapy treatment. Materials and methods: Patients diagnosed with recurrent CC subsequent to the failure of initial chemotherapy from January 2007 to December 2016 were enrolled from 2 hospitals. These patients were then divided into two groups: Group A, which underwent second-line chemotherapy alone, and Group B, which received both second-line chemotherapy and 125I brachytherapy. The assessment of overall survival (OS) and progression-free survival (PFS) was carried out through propensity score matching (PSM) (1:1), Kaplan-Meier curves, log-rank tests, and Cox proportional hazard regression for survival analysis. Results: A matched cohort comprising 88 patients each in Group A and Group B was included in the study. In Group A, the 1-, 2-, and 3-year cumulative PFS rates were 40.9 %, 15.9 %, and 5.7 % respectively, while in Group B, these rates were significantly higher at 79.5 %, 48.9 %, and 25.0 % (P = 0.003). Similarly, the 1-, 2-, and 3-year cumulative OS rates among Group A were 67.0 %, 27.3 %, and 5.7 % compared to 89.8 %, 63.6 %, and 30.7 % among Group B, suggesting a difference with statistical significance (P < 0.001) between the two groups. Moreover, the incidence of complications was similar between groups (P = 0.698). Conclusions: Our findings suggest that the combined approach of chemotherapy and 125I brachytherapy yields superior therapeutic effects but similar complication rates compared to chemotherapy alone in patients experiencing local recurrence of CC following failed initial chemotherapy.